Soustvarjanje pomoči v jeziku socialnega dela - Čačinovič Vogrinčič, Gabi (Socialno delo, 2010)
The central question od the article is: why are the development and use of social work language as a language of science and profession of social work important. In social work, a new, autonomous language is emerging, a language that translates well all steps taken in the process of help, envisaged as a co-creation based on ethics of participation and stranght perspective. Peter Luessi's systemic theory of social work is presented as the first important theory of doing and is related to contemporary, postmodern concepts of social work in a work relationship, bringing together appreciative and responsible allies (social workers) and experts on experience. The main thesis of the article can be summed up as: in science and profession of social work we need respectful steps and a disciplined use of social work language in theory and practice, at all times, without exceptions. The arguments in favour of the thesis are: social work language verbally expresses the way we do things; it brings forth changes; it is an appreciative language of co-creators in the process of help, taking into consideration strenght perspective; and it plays an important role in co-creation of joint projects with other professions.
Keywords: social work; socialno delo; pomoč; soustvarjanje; delovni odnos; etika udeleženosti; perspektiva moči